About counterttansference: ¿Obstacle or too!? - Corveleyn, Jozef (1997)
This paper discusses the different perspectives that exist in psychoanalysis about the status of the countertransference in the therapeutic process. On the one hand, for those who follow the classical tendency this should be radically repressed to protect the ideal of an aseptic neutrality. On the other hand, for those who follow the humanistic tendency, this should be incorporated to consolidate the externa! and real aspects of the therapeutic alliance. Together with the classical work uf Theodor Reik and the modero work of Harold Searles, the author proposes that countertransference feelings and reactions could be used as legitime tools to monitor both the relationship with the patient, as well as the interpretation phase.